2017
DOI: 10.7185/geochemlet.1730
|View full text |Cite
|
Sign up to set email alerts
|

Primary spinel + chlorite inclusions in mantle garnet formed at ultrahigh-pressure

Abstract: Multiphase inclusions represent microenvironments where the interaction between fluid and host mineral is preserved during the rock geological path. Under its peculiar chemical-physical constraints, the entrapped solute-rich fluid might follow a crystallisation mechanism which is not predictable through simple equilibrium arguments. In this letter, by the modelling of solid-solution equilibrium and the application of principles of mass conservation, we demonstrate that cavities in mantle garnet filled with sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Furthermore, the metasomatism of a peridotite by a granitic/granitoid melt is expected to cause abundant crystallization of orthopyroxene with the consequent formation of an Ol‐free garnet pyroxenite (Rampone & Morten, ). Even aqueous fluids of eclogitic origin can crystalize orthopyroxene in mantle rocks as demonstrated by natural examples (Malaspina et al, ), thermodynamic/mass balance studies (Campione, Tumiati, & Malaspina, ) and experimental works (Tiraboschi et al, ). RUB and KLA garnet clinopyroxene‐rich rocks are orthopyroxene‐free, and the production of garnet and clinopyroxene requires a high amount of CaO, an element which is instead not abundant: neither in the melt (CaO in the melt <1 wt%; see Table ) nor in Rubinberg and Klatschmühle peridotite (Schmädicke et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the metasomatism of a peridotite by a granitic/granitoid melt is expected to cause abundant crystallization of orthopyroxene with the consequent formation of an Ol‐free garnet pyroxenite (Rampone & Morten, ). Even aqueous fluids of eclogitic origin can crystalize orthopyroxene in mantle rocks as demonstrated by natural examples (Malaspina et al, ), thermodynamic/mass balance studies (Campione, Tumiati, & Malaspina, ) and experimental works (Tiraboschi et al, ). RUB and KLA garnet clinopyroxene‐rich rocks are orthopyroxene‐free, and the production of garnet and clinopyroxene requires a high amount of CaO, an element which is instead not abundant: neither in the melt (CaO in the melt <1 wt%; see Table ) nor in Rubinberg and Klatschmühle peridotite (Schmädicke et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Similar features in metasomatised suprasubduction peridotites have been described by Malaspina et al (2006) and Endo et al (2015) who demonstrated that replacive orthopyroxene derives by the reaction of the peridotite with a slab-derived silicate melt at HP/UHP. In addition, experimental results on olivine solubility in COH fluids (Tiraboschi et al, 2018) and mass balance modelling of solid-solution equilibrium between slab-derived aqueous fluids and garnet peridotite (Campione et al, 2017) indicate that also H 2 O-rich fluids released from a subducted eclogite are able to crystallise metasomatic orthopyroxene in the mantle. Whether the metasomatic agent responsible for the modal metasomatism of Monte Duria peridotites is a C-bearing silicate melt or an aqueous COH fluid (Hermann et al, 2006) must be searched in the associated crustal rocks and in their reconstructed P-T path.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion from CO 2 to C in the mantle gives a potential redox budget flux in the order of 10 11 mol year -1 , inducing the oxidation of the sub-arc mantle (Evans, 2012). The solubility of Fe 3+ in subduction zone fluids is not well known, even if the solute content of deep slab fluids may contain high Fe 3+ concentrations also after the interaction with the host mineral during the crystallization of the daughter phases (Campione et al, 2017;Malaspina et al, 2017).…”
Section: Slab-to-mantle Mass Transfer: Trace Elements and Redox Budgetmentioning
confidence: 99%